New Structural Patterns in Moribund Grammar: Case Marking in Heritage German - Yager, Lisa; Hellmold, Nora; Joo, Hyoun-A; Putnam, Michael T.; Rossi, Eleonora; Stafford, Catherine; Salmons, Joseph (Frontiers in Psychology, 2015)
Research treats divergences between monolingual and heritage grammars in terms of performance — ‘L1 attrition’, e.g. lexical retrieval — or competence — ‘incomplete acquisition’, e.g. lack of overt tense markers (e.g. Montrul 2008, Polinsky 1995, Schmid 2010, Sorace 2004). One classic difference between monolingual and Heritage German is reduction in morphological case in the latter, especially loss of dative marking. Our evidence from several Heritage German varieties suggests that speakers have not lost case, but rather developed innovative structures to mark it. More specifically, Heritage German speakers produce dative forms in line with established patterns of Differential Object Marking (Bossong 1985, 1991; Aissen 2003), suggesting a reallocated mapping of case. We take this as evidence for innovative reanalysis in heritage grammars (Putnam & Sánchez 2013). Following Kamp and Reyle (1993) and Wechsler (2011, 2014), the dative adopts a more indexical discourse function, forging a tighter connection between morphosyntax and semantic properties. Moribund grammars deploy linguistic resources in novel ways, beyond narratives of ‘attrition’ and ‘incomplete acquisition’.